2023
DOI: 10.3390/jof9070774
|View full text |Cite
|
Sign up to set email alerts
|

Germination of Microsporidian Spores: The Known and Unknown

Abstract: Microsporidia are a large group of mysterious obligate intracellular eukaryotic parasites. The microsporidian spore can survive in the absence of nutrients for years under harsh conditions and germinate within seconds under the stimulation of environmental changes like pH and ions. During germination, microsporidia experience an increase in intrasporal osmotic pressure, which leads to an influx of water into the spore, followed by swelling of the polaroplasts and posterior vacuole, which eventually fires the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 141 publications
(199 reference statements)
0
7
0
Order By: Relevance
“…In addition to ionic strength, the major factors affecting germination are the proteins on the spore wall, pH, osmotic pressure and temperature. 43 The findings herein revealed that UV radiation affects Nb germination in two ways. First, irradiation decreases the germination rate and reduces the number of germinable spores.…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations
“…In addition to ionic strength, the major factors affecting germination are the proteins on the spore wall, pH, osmotic pressure and temperature. 43 The findings herein revealed that UV radiation affects Nb germination in two ways. First, irradiation decreases the germination rate and reduces the number of germinable spores.…”
Section: Discussionmentioning
confidence: 76%
“…Once inside the host, the spores germinate and release their infectious contents, resulting in the establishment of the parasite within the host's cells. 42,43 The results of this study suggest that disrupting the permeability of the spore wall to allow trehalose leakage or altering the induction of spores to germination stimuli, thereby preventing spore germination, are mechanisms by which UV radiation acts on Nb spores, both of which are effective ways to stop Nb spore infection and ideas for developing new disinfection methods and controlling silk diseases.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…As a result, the existence of pathogen-derived PP1 within host cells may be of great importance for both pathogen cells’ intracellular proliferation and host cell manipulation. As for microsporidia, many species have been proved to possess this proteinase and exert important functions, for example, in germination ( 48 , 49 ). Our study is the first and very excited one to identify the E. hellem -derived serine/threonine PP1 and verify the direct interaction with host p38α (MAPK14) in the MAPK signaling pathway.…”
Section: Discussionmentioning
confidence: 99%